Encryption-Based Attack Detection Scheme for Multisensor Secure Fusion Estimation - Li, Tongxiang; Weng, Pindi; Chen, Bo; Zhang, Dongping; Yu, Li (IEEE transactions on aerospace and electronic systems, 2024)
This article deals with the problem of secure fusion estimation for multisensor systems under false data injection (FDI) attacks, where each sensor node sends a local estimation to the fusion center through the communication network, and each local estimate may be subject to FDI attacks. First, a practical data encryption scheme with low computational complexity is designed in the transmission of local estimation to establish a dynamic relationship between ciphertext, secret key, and decryption value. In particular, this dynamic relationship will be changed once FDI attacks occur, which can be used to directly verify whether the local estimation is under attack. Then, an encryption-based attack detection scheme is designed to achieve immediate detection and location of FDI attacks according to the characteristics of data encryption scheme. Furthermore, based on the attack detection results, a secure fusion estimation algorithm is proposed to eliminate the impact of FDI attacks on fusion estimation accuracy. Finally, a simulation example is given to show the effectiveness of the proposed secure fusion estimation algorithm.